Analisis Perilaku Konsumen dan Pengaruh Atribut Produk terhadap Keputusan Pembelian Sambal Olahan Merek Emak Ti dan Dede Satoe di Surabaya - Maulida Kurnia Sari Marpaung; Dyah Erni Widyastuti (Universitas Muhammadiyah Malang, 2018)
The competition between processed chili businessmen is currently very tight, especially in the Surabaya area. where in the area there have been many home industries to promote superior products in the form of processed chili sauce in packaging. This condition encourages business people to innovate and develop related to purchasing behavior, consumer characteristics, and various advantages of product attributes.The purpose of this study is to 1) Know the characteristics of consumers who buy processed chilli products, 2) Know the consumer decision-making process in the purchase of processed chilli products, 3) Know the attributes that differentiate consumer decisions in buying processed chili products Brand Emak Ti and Dede Satoe . This type of research is qualitative descriptive using primary data. Data analysis method used is descriptive and discriminant analysis. The results of this study are: 1) The majority of consumers who purchase processed chili products are women who live in Surabaya and have an age range of 31-40 years, most of them work as private employees with an income of Rp.2,000.001-Rp.3,000,000 per the month. 2) Consumers make purchasing decisions through five stages, starting from need recognition, information search, alternative evaluation, purchase, to behavior after buying. 3) Attributes that differentiate are price, quality, brand and packaging.